Thioglycosides Are Efficient Metabolic Decoys of Glycosylation that Reduce Selectin Dependent Leukocyte Adhesion. Issue 12 (20th December 2018) - Wang, Shuen-Shiuan; Gao, Xuefeng; Solar, Virginia del; Yu, Xinheng; Antonopoulos, Aristotelis; Friedman, Alan E.; Matich, Eryn K.; Atilla-Gokcumen, G. Ekin; Nasirikenari, Mehrab; Lau, Joseph T.; Dell, Anne; Haslam, Stuart M.; et al.
Summary: Metabolic decoys are synthetic analogs of naturally occurring biosynthetic acceptors. These compounds divert cellular biosynthetic pathways by acting as artificial substrates that usurp the activity of natural enzymes. While O-linked glycosides are common, they are only partially effective even at millimolar concentrations. In contrast, we report that N-acetylglucosamine (GlcNAc) incorporated into various thioglycosides robustly truncate cell surface N- and O-linked glycan biosynthesis at 10–100 μM concentrations. The >10-fold greater inhibition is in part due to the resistance of thioglycosides to hydrolysis by intracellular hexosaminidases. The thioglycosides reduce β-galactose incorporation into lactosamine chains, cell surface sialyl Lewis-X expression, and leukocyte rolling on selectin substrates including inflamed endothelial cells under fluid shear. Treatment of granulocytes with thioglycosides prior to infusion into mouse inhibited neutrophil homing to sites of acute inflammation and bone marrow by ∼80%–90%. Overall, thioglycosides represent an easy to synthesize class of efficient metabolic inhibitors or decoys. They reduce N-/O-linked glycan biosynthesis and inflammatory leukocyte accumulation. Graphical Abstract: Highlights: S-Glycosides act as superior metabolic decoys compared with O-glycosides Unlike O-glycosides, the S-glycosides resist hydrolysis by cellular hexosaminidases S-Glycosides reduce sialyl Lewis-X expression and E-selectin binding to neutrophils S-Glycosides block granulocyte migration to mouse bone marrow and inflammation sites Abstract : Small-molecule inhibitors of glycosylation can be applied in basic science studies, and clinical investigations as anti-inflammatory, anti-metastatic, and anti-viral therapies. This article demonstrates that thioglycosides represent a class of potent metabolic decoys that resist hydrolysis, and block E-selectin-dependent leukocyte adhesion in models of inflammation.